Stock market of Kazakhstan: current state and prospects of development (Journal of Economic Research & Business Administration, 2015)
The stock market is the main mechanism of redistribution of capital between sectors and actors of the economy and has a signifi cant impact on the whole economy. After independence in 1991, Kazakhstan , as well as any other former Soviet republic, faced with an acute problem of forming new relationships in the economy and a fundamental transformation of all established business processes. Over the past 20 years the country’s stock market is undergoing many changes. Due to the effect of the securities market on the process of creating a stable and sustainable fi nancial system, its importance for Kazakhstan is obvious. Realizing this , the government pays great attention to the stock market, in particular President Nursultan Nazarbayev in his speeches repeatedly talked about the need for its development. Kazakhstan’s stock market is at a crossroads , but may soon become a truly effective and advanced tool. Achieving this goal will largely depend on the measures taken by the government to improve the investment climate in the country , increasing the number of new issuers , mobilization of fi nancial, public, and human development and the use of professional practices and developments.
Keywords: The stock market; shares; bonds; listed issuer